Application of Digital Electromyography Portable (DEP) In Arduino Uno Based Progressive Muscle Relaxation (PMR) Exercise in The Elderly - Eqlima Elfira; Bina Melvia Girsang; Nurbaiti Nurbaiti (EDUTEC : Journal of Education And Technology, 2022)
Progressive muscle relaxation exercise is an intervention carried out to train muscles to regularly move maximally. Technological developments in the 4.0 era made changes so that the elderly knew that the application of portable digital electromyography could be done at home. Muscular strength is the amount of force a muscle can produce with maximum effort. An electromyograph is used as an interrogator by measuring the sensory activity of the elderly muscles. Teacher performance in education is very important. There are several factors that influence teacher performance, namely factors from work motivation and work discipline. The purpose of this study was to determine the level of accuracy of the application of digital electromyography in the elderly. This research was conducted on 30 elderly who are in environment III, Medan Sunggal sub-district with a quasi-experimental research design with a pretest-postest design. The method used in this study is to use a questionnaire level of sophistication and weighting of technological components in the instrument. The analytical method used in this research is descriptive statistical analysis method. Based on data analysis in this study, the results showed that there were significant differences in the accuracy of the application of portable digital electromyography in the elderly with a value of r count = 0.453 r table = 0.44.